Blueberry Bud Mite, Acalitus vaccinii (Keifer) on Southern Highbush Blueberry in Florida - Elke Weibelzahl; Oscar E. Liburd (EDIS, 2010)
ENY858, a 3-page illustrated fact sheet by Elke Weibelzahl and Oscar E. Liburd, provides a guideline for the recognition and control of this mite (BBM) that is an important pest of Lowbush, highbush, and Rabbiteye blueberries in Florida. Includes references. Published by the UF Department of Entomology and Nematology, January 2010.